La motivación de los alumnos polacos para el aprendizaje del español como lengua extranjera - Małgorzata Spychała-Wawrzyniak; Leonor Sagermann Bustinza (Studia Romanica Posnaniensia, 2016)
Over the past several years the number of students learning Spanish as a foreign language has doubled in Poland. The present article is an attempt at answering the following questions: Why is Spanish so popular in Polish schools and what are the reasons for choosing this language by Polish students? The authors wish to analyze the situation from the point of view of two types of motivation: internal (integral) motivation and external (instrumental) motivation. The results of our study have been compared to the results of corresponding studies carried out among Polish students learning German. At the opening of our deliberations we present the definitions and typical features of motivation. Next the typology and origin of motivation is discussed, which incorporates both the cognitive and affective approach. Finally, we submit the results of a pilot study performed among Polish middle school and high school students who learn Spanish.